2014
DOI: 10.5005/jp-journals-10006-1293
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fetal Reduction in Triplet Pregnancy: Indian Experience — A Retrospective Review of 32 Cases

Abstract: Aim:To review the effects of selective fetal reduction in trichorionic triplet pregnancy with focus on risk of miscarriage and preterm delivery in Indian women and thus provide local data for counseling the prospective parents in similar situation. Materials and methods:This retrospective study reviewed the pregnancy outcome of 32 sets of triplet pregnancies following fetal reduction. All mothers had trichorionic triplet pregnancy with three live fetuses at 10 to 11 weeks of gestation. One to two milliliter ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…In our case series, the mean maternal age was 25.75 years which was much lower than the mean maternal age in the studies conducted by 33.68±3.09 years [5] and Chaudhury and Mukherjee (31.90±4.11 years) who conducted a retrospective study of 32 triplet pregnancies that had undergone fetal reduction with KCl and their maternal and perinatal outcomes [6]. The mean gestational age at which the fetal reduction was done was 13+1 weeks, after a detailed nuchal translucency scan, to rule out gross congenital anomalies.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…In our case series, the mean maternal age was 25.75 years which was much lower than the mean maternal age in the studies conducted by 33.68±3.09 years [5] and Chaudhury and Mukherjee (31.90±4.11 years) who conducted a retrospective study of 32 triplet pregnancies that had undergone fetal reduction with KCl and their maternal and perinatal outcomes [6]. The mean gestational age at which the fetal reduction was done was 13+1 weeks, after a detailed nuchal translucency scan, to rule out gross congenital anomalies.…”
Section: Discussioncontrasting
confidence: 63%
“…They had not included the patients who underwent a reduction of triplets to singleton pregnancies. The mean gestational age to which the women carried to live birth was 28+2 weeks which was less compared to the mean gestational ages in the studies by Kumawat et al [5], Chaudhury and Mukherjee [6], Antsaklis et al [7], and Boulot et al [8].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A retrospective analysis of selective fetal reduction in triplet pregnancy reported 3.12% pregnancy loss occurring before 24 weeks of pregnancy. 9 A recent study from china has reported an abortion rate of 31% when fetal reduction was undertaken at 16 to 14 weeks when compared to 8.8% abortion rate when the same procedure was undertaken between 12 to 13 +6 days and 15.6% when performed between 14-15 +6 weeks. 10 Most of the studies in literature reported on the usage of inj.…”
Section: Discussionmentioning
confidence: 99%
“…In an another study, from India, 32 sets of trichorionic triplets were reduced to twins at 10-11 weeks. Complete pregnancy loss at \24 weeks occurred in 3.12% [10]. The authors reported that 48.3% of pregnancies carried beyond 35 weeks.…”
Section: Pregnancy Outcomementioning
confidence: 97%